Refinement of Neuronal Synchronization with Gamma Oscillations in the Medial Prefrontal Cortex after Adolescence - de Almeida, Julián (Public Library of Science, 2013)
The marked anatomical and functional changes taking place in the medial prefrontal cortex (PFC) during adolescence set grounds for the high incidence of neuropsychiatric disorders with adolescent onset. Although circuit refinement through synapse pruning may constitute the anatomical basis for the cognitive differences reported between adolescents and adults, a physiological correlate of circuit refinement at the level of neuronal ensembles has not been demonstrated. We have recorded neuronal activity together with local field potentials in the medial PFC of juvenile and adult mice under anesthesia, which allowed studying local functional connectivity without behavioral or sensorial interference. Entrainment of pyramidal neurons and interneurons to gamma oscillations, but not to theta or beta oscillations, was reduced after adolescence. Interneurons were synchronized to gamma oscillations across a wider area of the PFC than pyramidal neurons, and the span of interneuron synchronization was shorter in adults than juvenile mice. Thus, transition from childhood to adulthood is characterized by reduction of the strength and span of neuronal synchronization specific to gamma oscillations in the mPFC. The more restricted and weak ongoing synchronization in adults may allow a more dynamic rearrangement of neuronal ensembles during behavior and promote parallel processing of information.